Development and evaluation through structural equation modeling of a model of healthy behaviours in older adults - Sullivan, Shannon M (University of Ottawa (Canada), 2006)
Unhealthy behaviours contribute significantly to chronic disease. Longitudinal studies report improvements in the health of older adults after positive changes in health behaviours. A conceptual model of healthy behaviours in older adults was developed based on prospective evidence. Structural equation modeling was used to test specific hypotheses in a sample of 980 family practice patients over 65 years who attended a cardiovascular health awareness session. A model was specified that included variables reflecting health status, health-related quality of life, physician counseling and patient knowledge (p=0.02, CFI=0.97, RMSEA=0.039). Health-related quality is the most important pathway to healthy lifestyle behaviours (beta=0.41). Physician counseling is the most important pathway to healthy self-care behaviours (beta=0.64). This preliminary model provides evidence of the importance of health-related quality of life and physician counseling for influencing healthy behaviours among older adults.
Keywords: Biology, Biostatistics.; Gerontology.; Health Sciences, Public Health.